2006
DOI: 10.1093/cercor/bhj135
|View full text |Cite
|
Sign up to set email alerts
|

GABA-A Receptors Regulate Neocortical Neuronal Migration In Vitro and In Vivo

Abstract: The cortical migration process depends on a number of trophic factors and on the activation of different voltage- and ligand-gated channels. We investigated the role of gamma-aminobutyric acid (GABA) type A receptors in the neuronal migration process of the newborn rat parietal cortex in vivo and in vitro. Local in vivo application of the GABA-A antagonist bicuculline methiodide (BMI) or the agonist muscimol via cortical surface Elvax implants induced prominent alterations in the cortical architecture when com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
114
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 47 publications
4
114
0
Order By: Relevance
“…However, two recent studies provide some additional support for this finding. Heck et al (2007) found that application of the GABA A receptor antagonist, bicuculline, induced an increase in the migration speed of cortical neurons in organotypic neocortical slices from embryonic day 18-19. This increase in speed resulted in aberrant accumulation of neurons in the upper cortical layers.…”
Section: Gaba: a Negative Regulator Of Neuroblast Production In The Svzmentioning
confidence: 93%
“…However, two recent studies provide some additional support for this finding. Heck et al (2007) found that application of the GABA A receptor antagonist, bicuculline, induced an increase in the migration speed of cortical neurons in organotypic neocortical slices from embryonic day 18-19. This increase in speed resulted in aberrant accumulation of neurons in the upper cortical layers.…”
Section: Gaba: a Negative Regulator Of Neuroblast Production In The Svzmentioning
confidence: 93%
“…Local in vivo application of bicuculline methiodide via cortical surface Elvax implants revealed heterotopic cell clusters in the upper layers (264). In organotypic neocortical slices from embryonic day 18 -19 embryos, bicuculline increased the migration speed, suggesting an inhibitory action of GABA on migration (264).…”
Section: Gaba Modulates Neuronal Migrationmentioning
confidence: 95%
“…Of particular interest is the role of neurotransmitters in the regulation of activity-dependent mechanisms of synaptogenesis. During corticogenesis, the principal adult inhibitory neurotransmitter GABA influences the processes of cell proliferation, migration, and differentiation (Barbin et al, 1993;LoTurco et al, 1995;Heck et al, 2007). GABAergic signaling precedes glutamatergic signaling in the developing neocortex because newborn neurons express GABA A receptors (GABA A Rs) and receive GABAergic inputs from striatally derived interneurons before forming glutamatergic synapses with each other (Owens et al, 1999;Hennou et al, 2002).…”
Section: Introductionmentioning
confidence: 99%